Recent Publications (Quarterly Journal of Economics, 1963)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 77, Issue 4, November 1963, Pages 701–704, https://doi.org/10.1093/qje/77.4.701 Published: 01 November 1963